2016
DOI: 10.1111/jcpe.12487
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser for harvesting de‐epithelialized palatal graft in the treatment of gingival recession defects: a randomized clinical trial

Abstract: While both techniques were effective with regard to root coverage at 6 months, the DGG-L technique decreased post-operative morbidity associated with palatal donor-site surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 30 publications
2
46
0
4
Order By: Relevance
“…Some clinical studies have also shown the benefits of this therapeutic modality in the oral mucosa of humans [15][16][17]. In a previous study, our group showed that the PBM using a 15 J/cm 2 dosage was able to accelerate the palatal wound closure after connective tissue graft harvesting, compared to in patients who did not receive laser therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some clinical studies have also shown the benefits of this therapeutic modality in the oral mucosa of humans [15][16][17]. In a previous study, our group showed that the PBM using a 15 J/cm 2 dosage was able to accelerate the palatal wound closure after connective tissue graft harvesting, compared to in patients who did not receive laser therapy.…”
Section: Discussionmentioning
confidence: 95%
“…The results showed that the laser may have additional beneficial effects for this type of procedure [15,16]. Another recent study that evaluated the PBM effects in the palatal area after the removal of connective tissue graft to treat gingival recessions observed that patients treated with a dose of 15 J/cm 2 had accelerated closure of their surgical wound and decreased tissue repair time, compared with patients who did not receive laser therapy [17].…”
Section: Introductionmentioning
confidence: 93%
“…Ozturan et al 25 also showed statistically significant differences when LLLT was applied to test sites after CAF procedures for treatment of multiple recession‐type defects. Other studies confirm the short‐term positive results after LLLT irradiation in semilunar CAF procedures 26 and in healing wounds of the palatal mucosa following CT harvest 27 , 28 , 39 . However, there is no evidence on the long‐term stability of these outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, despite beneficial effects of LLLT in the short term, in the long term LLLT may add very limited or no additional benefit to the CAF+CTG technique. It may benefit less predictable techniques rather than CAF+CTG, 25 or it may be useful to accelerate the healing of the donor site, as previously shown 27 , 28 , 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation